If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2x + -6) = -112 Reorder the terms: 8(-6 + 2x) = -112 (-6 * 8 + 2x * 8) = -112 (-48 + 16x) = -112 Solving -48 + 16x = -112 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 16x = -112 + 48 Combine like terms: -48 + 48 = 0 0 + 16x = -112 + 48 16x = -112 + 48 Combine like terms: -112 + 48 = -64 16x = -64 Divide each side by '16'. x = -4 Simplifying x = -4
| -33=-5(6n+3) | | 10(y-8)=-30 | | 11x+2x=91 | | 3(n-7)=-7 | | 14-2(4x-8)=6 | | 6(x+3)+6=42 | | 2x+3=5x+8 | | 5r^2-20r-9=6 | | 3w(11w+8)= | | 5r^2-20r-9=0 | | 13.62+.13(x+3)=14.37-.09x | | xsquare(x+5)(x-5)=0 | | 1600x=20 | | 3y+17=62 | | y+19=192 | | f(-6)=7-2x | | 4x+14=5x | | 2x=6(2x-2)-5 | | 13.62+.13(x+3)=14.37+.09x | | 3(3+1)=(9-2x) | | 6n=(n+5) | | 30=-8x+2(x-6) | | y=mx+bfindx | | x^1/4=2 | | 5x-15=2x+20 | | 90+3+x+x-8=180 | | 10n-0.75=0.1n-0.375 | | 2-7g=2-g | | 2e^3x-9=0 | | 12a=3a+2.5a+a | | -1=6x-31 | | 15.93+.09(x+3)=16.43-.13x |